B-LINK: A hemicentin, plakin and integrin-dependent adhesion system that links tissues by connecting adjacent basement membranes - Morrissey, Meghan A. (Dev Cell, 2014)
Basement membrane (BM), a sheet-like form of extracellular matrix, surrounds most tissues. During organogenesis specific adhesions between adjoining tissues frequently occur, however their molecular basis is unclear. Using live-cell imaging and electron microscopy we identify an adhesion system that connects the uterine and gonadal tissues through their juxtaposed BMs at the site of anchor cell (AC) invasion in C. elegans. We find that the extracellular matrix component hemicentin (HIM-4), found between BMs, forms punctate accumulations under the AC and controls BM linkage to promote rapid invasion. Through targeted screening we identify the integrin-binding cytolinker plakin (VAB-10A) and integrin (INA-1/PAT-3) as key BM-BM linkage regulators: VAB-10A localizes to the AC-BM interface and tethers hemicentin to the AC while integrin promotes hemicentin punctae formation. Together, plakin, integrin and hemicentin are founding components of a cell-directed adhesion system, which we name a B-LINK (Basement membrane-LINKage), that connects adjacent tissues through adjoining BMs.